Avaliação dos efeitos letal e subletais do óleo oriundo do acidente ocorrido no litoral pernambucano em invertebrados marinhos - NASCIMENTO, Estefani Santana do (2022)
The present study aimed to evaluate the effect of the soluble and crude fraction of the oil, which contaminated the Brazilian coast in the accident that occurred in 2019, on aquatic microcrustaceans. For this, ecotoxicological bioassays were carried out, using the benthic copepod as a test organism.Thisbe biminiensis.The bioassays with the crude fraction of the oil lasted for 1 month, with a weekly water change. 0.5 g of oil collected from 5 different beaches on the coast of Pernambuco (Enseada dos Corais, Xaréu, Cupe, Paiva and Suape), 40 mL of filtered sea water and basic ration for macerated aquarium fish were used. The bioassays with the soluble fraction of the oil lasted for 7 days, using the same proportion of the crude fraction and the same test organism. At the end of the exposure period, the content was fixed with formaldehyde and stained with Rose Bengal, for subsequent counting and determination of endpoints (number of copepods, population number and percentage of females). Observations in the stereomicroscope revealed stains in the individuals, due to this fact, a new bioassay with the crude fraction of the oil was carried out for photographic recording under the same conditions as the previous one. At this stage, at the end of the exposure period, the content was not stained with Rose Bengal for an integral observation of the microcrustacean body and confirmation of the presence of oil through the microscope. The results showed a significant decrease in the number of copepods (in the groups exposed to the oil collected in Xaréu, Enseada dos Corais and Paiva) and in the population number (in all oil samples tested). In addition, there was a feminization of the population, where it was possible to notice a significant increase in the proportion of females in oil samples collected at Paiva beach and Enseada dos Corais. Through the photographic records it was verified that the oil was ingested by the studied species, part of which contaminated the animal, and the other part was fragmented and eliminated in the fecal pellets, becoming available for other organisms. In the experiment with the soluble fraction of the oil, the survival of the organisms exposed to the bioassay was evaluated. The results showed no lethal effects in the exposed groups. Thus suggesting that the oil did not release its soluble fraction into seawater during the process of obtaining it, and consequently, did not interfere with the survival of organisms. Therefore, it was concluded that the oil which contaminated the Brazilian coast has a high toxic power for the tested organism, due to the reduction in the average number of copepods, population decline, as well as the feminization of the population. becoming available to other organizations. In the experiment with the soluble fraction of the oil, the survival of the organisms exposed to the bioassay was evaluated. The results showed no lethal effects in the exposed groups. Thus suggesting that the oil did not release its soluble fraction into seawater during the process of obtaining it, and consequently, did not interfere with the survival of organisms. Therefore, it was concluded that the oil which contaminated the Brazilian coast has a high toxic power for the tested organism, due to the reduction in the average number of copepods, population decline, as well as the feminization of the population. becoming available to other organizations. In the experiment with the soluble fraction of the oil, the survival of the organisms exposed to the bioassay was evaluated. The results showed no lethal effects in the exposed groups. Thus suggesting that the oil did not release its soluble fraction into seawater during the process of obtaining it, and consequently, did not interfere with the survival of organisms. Therefore, it was concluded that the oil which contaminated the Brazilian coast has a high toxic power for the tested organism, due to the reduction in the average number of copepods, population decline, as well as the feminization of the population. The results showed no lethal effects in the exposed groups. Thus suggesting that the oil did not release its soluble fraction into seawater during the process of obtaining it, and consequently, did not interfere with the survival of organisms. Therefore, it was concluded that the oil which contaminated the Brazilian coast has a high toxic power for the tested organism, due to the reduction in the average number of copepods, population decline, as well as the feminization of the population. The results showed no lethal effects in the exposed groups. Thus suggesting that the oil did not release its soluble fraction into seawater during the process of obtaining it, and consequently, did not interfere with the survival of organisms. Therefore, it was concluded that the oil which contaminated the Brazilian coast has a high toxic power for the tested organism, due to the reduction in the average number of copepods, population decline, as well as the feminization of the population.